Dysfunctional purinergic signaling correlates with disease severity in COVID-19 patients - Pietrobon, Anna Julia; Andrejew, Roberta; Custódio, Ricardo Wesley Alberca; Oliveira, Luana de Mendonça; Scholl, Juliete Nathali; Teixeira, Franciane Mouradian Emidio; de Brito, Cyro Alves; Glaser, Talita; Kazmierski, Julia; Goffinet, Christine; Turdo, Anna Claudia; Yendo, Tatiana; et al. (Frontiers in Immunology, 2022)
Ectonucleotidases modulate inflammatory responses by balancing extracellular ATP and adenosine (ADO) and might be involved in COVID-19 immunopathogenesis. Here, we explored the contribution of extracellular nucleotide metabolism to COVID-19 severity in mild and severe cases of the disease. We verified that the gene expression of ectonucleotidases is reduced in the whole blood of patients with COVID-19 and is negatively correlated to levels of CRP, an inflammatory marker of disease severity. In line with these findings, COVID-19 patients present higher ATP levels in plasma and reduced levels of ADO when compared to healthy controls. Cell type-specific analysis revealed higher frequencies of CD39+ T cells in severely ill patients, while CD4+ and CD8+ expressing CD73 are reduced in this same group. The frequency of B cells CD39+CD73+ is also decreased during acute COVID-19. Interestingly, B cells from COVID-19 patients showed a reduced capacity to hydrolyze ATP into ADP and ADO. Furthermore, impaired expression of ADO receptors and a compromised activation of its signaling pathway is observed in COVID-19 patients. The presence of ADO in vitro, however, suppressed inflammatory responses triggered in patients’ cells. In summary, our findings support the idea that alterations in the metabolism of extracellular purines contribute to immune dysregulation during COVID-19, possibly favoring disease severity, and suggest that ADO may be a therapeutic approach for the disease.